Influence of Co3O4 Nanostructure Morphology on the Catalytic Degradation of p-Nitrophenol - Chen, Huihui; Yang, Mei; Liu, Yuan; Yue, Jun; Chen, Guangwen (Molecules (Basel, Switzerland), 2023)
The design and fabrication of nanomaterials with controllable morphology and size is of critical importance to achieve excellent catalytic performance in heterogeneous catalysis. In this work, cobalt oxide (Co3O4) nanostructures with different morphologies (nanoplates, microflowers, nanorods and nanocubes) were successfully constructed in order to establish the morphology–property–performance relationship of the catalysts. The morphology and structure of the nanostructured Co3O4 were characterized by various techniques, and the catalytic performance of the as-prepared nanostructures was studied by monitoring the reduction of p-nitrophenol to p-aminophenol in the presence of excess NaBH4. The catalytic performance was found to be strongly dependent on their morphologies. The experimental results show that the pseudo-first-order reaction rate constants for Co3O4 nanostructures with various shapes are, respectively, 1.49 min−1 (nanoplates), 1.40 min−1 (microflowers), 0.78 min−1 (nanorods) and 0.23 min−1 (nanocubes). The Co3O4 nanoplates exhibited the highest catalytic activity among the four nanostructures, due to their largest specific surface area, relatively high total pore volume, best redox properties and abundance of defect sites. The established correlation between morphology, property and catalytic performance in this work will offer valuable insight into the design and application of nanostructured Co3O4 as a potential non-noble metal catalyst for p-nitrophenol reduction.